2019
DOI: 10.1039/c9ra05301h
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolizidine alkaloids quantified in soil and water using UPLC-MS/MS

Abstract: Pyrrolizidine alkaloids quantified in soil and water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…This research reports PAs from butterbur in surface water for the first time, and provides evidence for our starting hypothesis that PAs can naturally leach from butterbur into water and make it unsafe to drink. Several previous studies identified PAs as soil or surface water contaminants [70][71][72] . Experimentally determined octanol-water partition coefficients infer little potential PA sorption to soil 73 .…”
Section: Discussionmentioning
confidence: 99%
“…This research reports PAs from butterbur in surface water for the first time, and provides evidence for our starting hypothesis that PAs can naturally leach from butterbur into water and make it unsafe to drink. Several previous studies identified PAs as soil or surface water contaminants [70][71][72] . Experimentally determined octanol-water partition coefficients infer little potential PA sorption to soil 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of the alkaloids during storage is therefore likely. Initial nominal concentrations are used for all toxicity estimates due to the 1) stability of the alkaloids during the experimental period, and 2) a recovery study measuring alkaloid concentrations in spiked soils and water using the same method with shorter storage time showed >90% recovery (Hama & Strobel, 2019).…”
Section: Chemicalsmentioning
confidence: 99%
“…Little environmental data for the concentrations of alkaloids in soil or water is currently published, however, we found four studies measuring plant alkaloids in pore, drainage and surface water (Hama & Strobel, 2019;Günthardt et al, 2020;Hama, 2020;Hama & Strobel, 2020b). A total of 26 alkaloids were measured in these studies.…”
Section: Risk Of Lupins and Other Alkaloid-producing Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies revealed a large diversity of phytochemicals from different classes of compounds (e.g., formononetin, gramine and senecionine) in environmental samples such as water and soil [18,20,47] and concentrations exceeding thresholds of toxicological concern for drinking water (TTC) [42] in water bodies from natural and agricultural areas. Assuming that only a minor fraction of SPMs in surface waters is known, considering these compounds in water quality monitoring and assessment may not rely on target screening only [9,11,18,20,47]. Here, non-target screening is helpful to access also unknown and unnoticed contaminants such as SPMs using liquid chromatography coupled to high-resolution mass spectrometry LC-HRMS) detecting as many contaminants as possible in parallel.…”
Section: Introductionmentioning
confidence: 99%